2017
DOI: 10.1021/jacs.7b07836
|View full text |Cite
|
Sign up to set email alerts
|

A Streptococcus pneumoniae Type 2 Oligosaccharide Glycoconjugate Elicits Opsonic Antibodies and Is Protective in an Animal Model of Invasive Pneumococcal Disease

Abstract: Invasive pneumococcal diseases (IPDs) remain the leading cause of vaccine-preventable childhood death, even though highly effective pneumococcal conjugate vaccines (PCVs) are used in national immunization programs in many developing countries. Licensed PCVs currently cover only 13 of the over 90 serotypes of Streptococcus pneumoniae (Sp), so nonvaccine serotypes are a major obstacle to the effective control of IPD. Sp serotype 2 (ST2) is such a nonvaccine serotype that is the main cause of IPD in many countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Minimal protective glycan epitopes are identified using synthetic homogeneous oligosaccharides that constitute one or more repeating units of bacterial CPS. Glycoconjugates containing such synthetic antigens have been previously tested individually for their antigenicity, immunogenicity, and protective effects in animal challenge models of disease, and have been shown to be effective in some cases (9,10,(17)(18)(19). We aimed to expand S. pneumoniae vaccine coverage by including serotype antigen conjugates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimal protective glycan epitopes are identified using synthetic homogeneous oligosaccharides that constitute one or more repeating units of bacterial CPS. Glycoconjugates containing such synthetic antigens have been previously tested individually for their antigenicity, immunogenicity, and protective effects in animal challenge models of disease, and have been shown to be effective in some cases (9,10,(17)(18)(19). We aimed to expand S. pneumoniae vaccine coverage by including serotype antigen conjugates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The medicinal chemistry approach has identified di-to tetrasaccharides as potential vaccine candidates (11). The immunogenicity of the CPS depends among other factors on rare sugars and labile functional groups (9,17,19). Stable oligosaccharide analogs can fix production problems such as those encountered for ST5 CPS due to the labile ketone present in the repeating unit (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly distinct determinants were identified in each case. Thus, in serotype 2 the GlcAα(1-6)Glcα(1-2) branch (GlcA being glucuronic acid) was found to be an important substructure of the hexasaccharide repeating unit (Emmadi et al, 2017), while in serotype 7F the two side chains that decorate the linear tetrasaccharide backbone, i.e., Galβ(1-and GlcNAcα(1-2)Rhaα(1-, played a key role (Menova et al, 2018). Gal modification with a pyruvate ketal in the linear tetrasaccharide unit of serotype 4 was observed to be an important determinant, although pyruvate-independent epitopes were also unveiled (Geissner et al, 2016), whereas in the serotype 5 pentasaccharide unit the rare aminosugar N-acetyl-L-pneumosamine (PneuNAc, Figure 2) together with branched N-acetyl-L-fucosamine (FucNAc) were essential for antibody recognition and avidity (Lisboa et al, 2017).…”
Section: Bacterial Glycan Arrays For Identification Of Novel Vaccine mentioning
confidence: 97%
“…Emmadi et al [ 76 ] reported the synthesis of the repeating unit of ST2 CPS and of series of synthetic glycans containing portions of the ST2 CPS (compounds 87a – 93a ), in order to identify the protective oligosaccharide epitope. Hexasaccharide 89a (one repeating unit) was synthesized from disaccharides 94 , 95 , 96 via a [2+2+2] glycosylation strategy ( Figure 11 ).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%